2001
DOI: 10.1038/sj.onc.1204410
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 oncoprotein protects the human prostatic carcinoma cell line PC3 from TRAIL-mediated apoptosis

Abstract: The role of Bcl-2 in TRAIL-induced apoptosis has been investigated in lymphoid cells. Here we show that the human prostatic carcinoma cell line PC3 was sensitive to TRAIL treatment whereas PC3 overexpressing of Bcl-2 was resistant. TRAIL receptors ligation in PC3 activated caspases -2, -3, -7, -8, and -9, induced Bid processing, dissipation of mitochondrial transmembrane potential (DC m ), and cytochrome c release. We have detected caspases -8 and -3 only in the cytosolic fraction of cells, but caspases -2, -7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
3

Year Published

2002
2002
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
1
53
3
Order By: Relevance
“…The ability of proteasome inhibitors, including PS-341, to stimulate TRAIL-induced apoptosis has also been reported in other cell lines (Mitsiades et al, 2001;Franco et al, 2001). The effects of TRAIL on induction of apoptosis in human prostate cancer cells are known to be blocked by overexpression of Bcl-2 or Bcl-xL (Munshi et al, 2001;Roklin et al, 2001). However, we found that the combination of PS-341 and TRAIL overcame the block to mitochondrial participation in the apoptotic process mediated by overexpression of Bcl-xL.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The ability of proteasome inhibitors, including PS-341, to stimulate TRAIL-induced apoptosis has also been reported in other cell lines (Mitsiades et al, 2001;Franco et al, 2001). The effects of TRAIL on induction of apoptosis in human prostate cancer cells are known to be blocked by overexpression of Bcl-2 or Bcl-xL (Munshi et al, 2001;Roklin et al, 2001). However, we found that the combination of PS-341 and TRAIL overcame the block to mitochondrial participation in the apoptotic process mediated by overexpression of Bcl-xL.…”
Section: Discussioncontrasting
confidence: 52%
“…Resistance results from a number of factors including the absence of caspase 8 (Grotzer et al, 2000), increased AKT activity resulting from deletion of the PTEN phosphatase , or the absence of Bax (Deng et al, 2002). In addition, overexpression of Bcl-2 family members blocks TRAIL-induced apoptosis (Munshi et al, 2001;Roklin et al, 2001). The observation that the majority of TRAIL-resistant cell lines can be made TRAIL sensitive by treatment with protein synthesis inhibitors (Rieger et al, 1998;Wajant et al, 2000) implies that additional mechanisms regulating TRAIL resistance may exist.…”
Section: Introductionmentioning
confidence: 99%
“…50 Bcl-xL and Bcl-2 localize to the outer mitochondrial membrane and exert antiapoptotic effects by preventing the efflux of cytochrome c from the mitochondria. [51][52][53] Overexpression of Bcl-xL resulted in a significant reduction of toxicity induced by 4HPR alone or by the combination of 4HPR and TRAIL (Figure 8a). The measurement of Dc m , using DiOC 6 (3) as a marker of MPT, demonstrated that the overexpression of BclxL abrogated the MPT induced by each reagent alone and by the combination of 4HPR and TRAIL (Figure 8b).…”
Section: The Combination Of 4hpr and Trail Induces Caspase-mediated Amentioning
confidence: 99%
“…These results suggest that TRAIL-induced apoptosis is primarily dependent upon a mitochondria-independent pathway. However, there are also a number of reports which suggest that Bcl-2 can signi®cantly inhibit TRAIL cytotoxicity and that caspase 3, Bid and cytochrome c release are required for TRAIL-induced apoptosis Gong and Almasan, 2000;Munshi et al, 2001;Rokhlin et al, 2001;Thakkar et al, 2001). Thus this discrepancy needs to be clari®ed.…”
Section: Introductionmentioning
confidence: 98%